2019
DOI: 10.21203/rs.2.19755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum amyloid a, a potential biomarker both in serum and tissue, correlates with ovarian cancer progression

Abstract: Objective: Ovarian cancer is the most fatal gynecologic malignancy worldwide due to delayed diagnosis as well as recurrence and drug resistance. Thus, a new type of ovarian cancer treatment prediction biomarker is urgently needed to supplement existing tools. Methods: One hundred patients operated on due to ovarian tumor were enrolled in this study. Meanwhile, one hundred ovarian benign patients and thirty healthy women were selected as control groups. Levels of SAA, CA125 and HE4 were assessed using standard … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…34 Another study showed that SAAs, including SAA1 and SAA4, promoted OVCAR-3 cell migration by regulating matrix metalloproteinases (MMPs) and EMT, which may correlate with Akt pathway activation. 35 In addition, Chang et al reported that the levels of SAA1 were increased in OSCC patients with relapse. 36 In the current study, we identified, using RNA-seq screening, that SAA1 is the most significantly upregulated gene in arecoline-treated OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…34 Another study showed that SAAs, including SAA1 and SAA4, promoted OVCAR-3 cell migration by regulating matrix metalloproteinases (MMPs) and EMT, which may correlate with Akt pathway activation. 35 In addition, Chang et al reported that the levels of SAA1 were increased in OSCC patients with relapse. 36 In the current study, we identified, using RNA-seq screening, that SAA1 is the most significantly upregulated gene in arecoline-treated OSCC cells.…”
Section: Discussionmentioning
confidence: 99%